In-plane behaviour of earthen materials: A numerical comparison between adobe masonry, rammed earth and COB - Miccoli, Lorenzo (2017)
The paper presents a comparison between different numerical modelling approaches aiming to simulate the in-plain behaviour of three types of earthen materials, namely adobe masonry, rammed earth and cob. For this purpose, uniaxial and diagonal compression tests were carried out, which allowed determining important mechanical parameters, such as compressive strength, Young's modulus, Poisson's ratio, shear strength and shear modulus. Furthermore, the tests allowed assessing the level of non-linear behaviour of the respective stress-strain relationships as well as the failure modes. The experimental results were then used for the calibration of numerical models (based on the finite element method) for simulating the non-linear behaviour of the earth materials under in-plane shear loading. Both macro- and micro-modelling approaches were considered for this purpose. The procedures adopted for model calibration established the reliability of various modelling strategies for the different loading conditions. The simplified approach based on macro-modelling shows a satisfactory accuracy and low computational costs. The results reproducing the uniaxial compression are in good correspondence with the post-elastic behaviour observed in the experimental campaign. The micro-modelling approach adopted to reproduce the shear behaviour, even with higher computational cost, represents a suitable tool to predict the adobe masonry and rammed earth collapse mechanisms.